2016
DOI: 10.1681/asn.2016020131
|View full text |Cite
|
Sign up to set email alerts
|

SOS2 and ACP1 Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function

Abstract: Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (: 111,666; : 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…When morpholinos against these genes were injected into zebrafish embryos, there were morphological changes in the renal tubule seen, e.g. elongation, and there was also reduced body length overall of the embryo [72]. To ensure that these changes were not a result of off-target effects, the morpholinos directed against the ‘ATG’ start site were validated with splice site morpholinos which also show similar phenotypes such as the reduced body length [72].…”
Section: Zebrafish As a Model Of Glomerular Diseasementioning
confidence: 99%
“…When morpholinos against these genes were injected into zebrafish embryos, there were morphological changes in the renal tubule seen, e.g. elongation, and there was also reduced body length overall of the embryo [72]. To ensure that these changes were not a result of off-target effects, the morpholinos directed against the ‘ATG’ start site were validated with splice site morpholinos which also show similar phenotypes such as the reduced body length [72].…”
Section: Zebrafish As a Model Of Glomerular Diseasementioning
confidence: 99%
“…In nontransplant populations, there has been a number of large well-powered GWAS that have identified genetic variants that associate robustly with kidney function, [12][13][14][15] the largest of which (n = 133 814) was carried out by Pattaro et al 13 However, despite the identification of a number of risk loci, univariate effect sizes were small (beta coefficient of -0.00095 to 0.009 for the 24 novel loci identified).…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that about one third of the variation in eGFR levels can be attributed to genetic factors 8 , with the remaining variability due to environmental effects. Previous GWAS studies and meta-analyses have identified a number of loci associated with serum creatinine, eGFR, or CKD [9][10][11][12][13][14][15][16][17][18] . However, the introduction of denser imputation panels, including the Haplotype Reference Consortium 19 (HRC), and the recent rise in large-scale biobanks has enabled larger sample sizes and a greater number of variants than previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen of the 48 novel variants and 36 of the 85 lead variants in known loci that were available in the UK Biobank were at least nominally associated with one or more UK Biobank kidney-related phenotypes ( Supplementary Table 5). In addition, we compared the results from the current meta-analysis with previously reported eGFR index variants [9][10][11][12]14,15,17 . Of the 127 previously reported index variants for eGFR, 125 were at least nominally significant in the present meta-analysis (Supplementary Table 6) and 63% reached genome-wide significance (p-value < 5x10 -8 ).…”
Section: Introductionmentioning
confidence: 99%